2020
DOI: 10.1111/mmi.14664
|View full text |Cite
|
Sign up to set email alerts
|

The structure and mechanism of the bacterial type II secretion system

Abstract: The T2SS is a macromolecular complex that spans the cell envelope of many Gram-negative bacteria. It is part of a much larger superfamily of type IV filament containing systems all of which share homologous components and conserved mechanistic principles. These include the type 4a and 4b pilus (Craig et al., 2019), tight adherence (Tad) pilus (Tomich et al., 2007), mannose-sensitive hemagglutinin pilus (Marsh and Taylor, 1999), competence pilus (Piepenbrink, 2019) and archaeal T4 pilus and flagellum (Makarova … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 145 publications
(238 reference statements)
1
45
0
3
Order By: Relevance
“…sekretyna -białka OM, które oligomeryzują, tworząc pory wydzielnicze) [4,31]. Sekretyna złożona jest z czterech N-końcowych domen peryplazmatycznych (N0, N1, N2 i N3), rdzenia oraz C-końcowej domeny S [32]. Zakotwiczony w błonie wewnętrznej (IM) kompleks składający się z białek T2S F, -L oraz -M tworzy obejmujący peryplazmę kanał, powstały na skutek oddziaływania z sekretyną.…”
Section: Budowa II Systemu Sekrecjiunclassified
“…sekretyna -białka OM, które oligomeryzują, tworząc pory wydzielnicze) [4,31]. Sekretyna złożona jest z czterech N-końcowych domen peryplazmatycznych (N0, N1, N2 i N3), rdzenia oraz C-końcowej domeny S [32]. Zakotwiczony w błonie wewnętrznej (IM) kompleks składający się z białek T2S F, -L oraz -M tworzy obejmujący peryplazmę kanał, powstały na skutek oddziaływania z sekretyną.…”
Section: Budowa II Systemu Sekrecjiunclassified
“…Reports of stoichiometry range between twelve and fifteen monomers per complex, divided into a number of different domains. The C-terminal domain integrates into the bacterial outer membrane and forms a double-walled ß-barrel with a central gate forming a stricture at the centre 21 . Varying numbers of soluble N-domains connect to the ß-barrel and project into the periplasm.…”
Section: Introductionmentioning
confidence: 99%
“…The C-terminal domain integrates into the bacterial outer membrane and forms a doublewalled ß-barrel with a central gate forming a stricture at the centre 17 . Varying numbers of soluble N-domains connect to the ß-barrel and project into the periplasm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryo-electron microscopy (cryo-EM) of the secretin complexes revealed that these proteins share a similar architecture. A less-conserved N-terminal domain forms a periplasmic vestibule that interacts with the IM components of the virulence system, and a well-conserved C-terminal domain forms an OM channel with one or two gate structures (Weaver et al, 2020;Hu et al, 2018;D'Imprima et al, 2017;Naskar et al, 2021). Although secretin channels form much larger pore structures than the channels formed by a single polypeptide, it has been assumed that the gate structures of secretins prevent leakage of periplasmic contents and permeation of extracellular chemicals when they are not in use for protein secretion or pilus assembly (Majewski et al, 2018;Korotkov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%